Self Management Program Meningkatkan Koping, Niat dan Kepatuhan Berobat Pasien PJK - Hanim Mufarokhah; Suhartono Taat Putra; Yulis Setiya Dewi (Universitas Airlangga, 2016)
Introduction: Management coronary artery disease required lifelong treatment. The successful management of CHD requires efective coping, intention and medication adherence of CHD’s patients. This study aimed to explain the changes of coping, intention, and medication adherence in patients with CHD after giving self management programme in RSUD Jombang based on Theory Planned Behavior.Methods: This study used a quasy experimental pretest-posttest control group design and 28 respondens selected by consecutive sampling. Independent variable was self management programme while dependent variables were coping, intention, medication adherence. Data were collected by using questonnaires measuring coping level, intention and medication adherence. The statistical test used was Mann Whitney, Wilcoxone Signed Rank and t-Test.Results: The result showed that 1) self management programme improve the level of coping in patients with CHD (p < 0,001), 2) self management programme improve the level of intention in patients with CHD (p < 0,001), 3) self management programme improve the level of medication adherence in patients with CHD (p < 0,001).Conclusion: To change a behavior requires improvement of coping and intentions. This is in according to the Theory of Planned Behavior that behavior change is influenced by the attitude toward the behavior, subjective norm, perceived behavioral control and intention.